A&T Bangladesh Urban Maternal Nutrition Endline Survey 2022: Healthcare Provider - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset is the result of the Healthcare Provider survey that was conducted to gather data for the endline part of the impact evaluation study of the Alive & Thrive (A&T) interventions delivered through the Urban Maternal, Neonatal and Child Health (MNCH) Services in Bangladesh. These include building capacity for health providers and nutritional counselors in urban health clinics, creating a friendly environment for maternal, infant, and young child nutrition (MIYCN) counseling in clinic settings, community mobilization for demand creation of MIYCN services, interpersonal counseling on diet during pregnancy and consumption of iron-folic acid (IFA) and calcium, promotion of adequate weight-gain monitoring during pregnancy, and counseling on breastfeeding and complementary feeding practices.